Numerical simulation of heat-and-mass transfer processes in artificial burning CO^ gases cleanup systems - A. P. Nesenchuk; V. M. Kopko; T. V. Ryzhova; M. G. Pshonik; N. G. Malkevich (Литьë и металлургия)
On the basis of numerical simulation of heat-and- mass transfer dependencies of mass-transfer characteristics of αϒ and  αΩ sorption system at varying machine parameters are received.